TURKEY’S NEW FOREIGN POLICY LANDMARKS AND CENTRAL ASIA - YULDASHEVA, Guli (CENTRAL ASIA AND THE CAUCASUS, 2008)
The geopolitical tension that became even more evident in the wake of the 2001 events, the de facto unfolding global war over energy sources and transportation corridors in the Middle East and Central Asia, and certain aspects of Turkey’s domestic developments have greatly altered Ankara’s international status, its political weight, and its role.The victory of the candidate from the Pro Islamic Justice and Development Party (JDP) at the 28 August, 2007 presidential election created tension between the Islamic circles and the Turkish generals, since the JDP posed itself as the custodian of Kemal Atatürk’s traditional principles of a secular state.1 Today, however, the party is no longer perceived as another Islamic party, but rather as a conservative party resolved to blend Islam with the Turkish model and contemporary developments.2 It seems that the outcome of the latest presidential election was not paradoxical and perfectly fit the current global trends in the Islamic world, on the one hand, and was a logically justified response of the Turkish electorate to the post-2001 international developments, on the other. The party’s obvious and growing popularity testifies that the nation is more or less united on the republic’s foreign policy aims and its relative continuity.The steadily increasing dependence on energy resources suggests that Ankara should concentrate on ensuring an adequate level of the republic’s energy security. Indeed, nearly all the planned thermal power stations, which are expected to produce over 63 percent of energy in the republic, will use imported coal and gas. According to certain experts,3 continued economic growth in Turkey and the need to bring its infrastructure to the EU level will increase the country’s dependence on imported energy to become, in the final analysis, the “professional aptitude test” of the JDP Cabinet.